Synthesis and characterization of poly(vinyl alcohol): Cloisite® 20A nanocomposites. Issue 3 (22nd June 2015) - Al‐Marri, M.J.; Masoud, M.S.; Nassar, A.M.G.; Zagho, M.M.; Khader, M.M.
Abstract : Polymeric nanocomposite materials are very important materials because of their promised applications. However, many of their fundamental physical, mechanical, and chemical behaviors have not been quantified. Depending on the interface forces between polymer and clay, different configurations of polymer–clay nanocomposites exist: intercalated, flocculated, and exfoliated nanocomposites. In this paper, a study on the first two configurations is presented. Poly(vinyl alcohol) (PVA)–Cloisite ® 20A was chosen for the intercalated system and PVA–Cloisite ® 10A was chosen for the flocculated one. In both cases, the phyllosilicate clays used were organically modified by tallow‐triethanol‐ammonium ion. The morphology of the two systems was investigated by using X‐ray diffraction and nanoscanning electron microscopy. Although both confirmed the intercalation between PVA and 20A nanoclay, they confirmed the nonintercalation between PVA and 10A nanoclay. Another confirmation of the intercalation phenomena in PVA and 20A nanoclay was obtained from differential scanning calorimetry, which showed an increase in crystallinity upon intercalation. A main focus for the intercalated system was to study the effect of the nanoparticle's loading on the mechanical properties. Intercalation markedly affected both Young's modulus and the extent of elongation of the PVA–Cloisite ® 20A nanocomposite. Young's modulus and tensile stress increased with the loading of the clay up to 2 wt%. For higher loading, opposite results were reported due to the agglomeration of nanoparticles and as a consequence of the formation of microvoids. J. VINYL ADDIT. TECHNOL., 23:181–187, 2017. © 2015 Society of Plastics Engineers